2015
DOI: 10.1002/pbc.25563
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea use in prevention of stroke recurrence in children with sickle cell disease in a developing country: A cost effectiveness analysis

Abstract: We undertook a cost effectiveness analysis (CEA) of hydroxyurea (HU) in preventing stroke recurrence and/or death. We followed 43 children with sickle cell disease from 2000 to 2009 after having a first clinical stroke, of whom 10 opted for HU therapy. HU use led to decreased stroke recurrence and death without significantly increasing the annual cost of care per patient (J$83,250 vs. J$76,901, P = 0.491). The incremental cost effectiveness ratio (ICER) for prevention of stroke recurrence amounted to J$169,238… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…It has been shown to reduce the frequency of acute painful episodes, dactylitis, acute chest syndrome, hospitalizations, and the need for blood transfusions in children and adults with sickle cell anemia (161,162). Observational studies have reported a reduction of TCD velocity (163165), rate of first stroke (166) and the rate of stroke recurrence (167170) in SCD patients treated with hydroxyurea. The Stroke With Transfusions Changing to Hydroxyurea (SWiTCH) trial, was a randomized, non-inferiority trial comparing transfusions and iron chelation to hydroxyurea and therapeutic phlebotomy for children with sickle cell anemia, stroke, and iron overload, with a composite primary endpoint allowing an increased stroke risk but requiring superiority for removing iron (171).…”
Section: Effect Of Disease Modifying Treatments Anticoagulants Anmentioning
confidence: 99%
“…It has been shown to reduce the frequency of acute painful episodes, dactylitis, acute chest syndrome, hospitalizations, and the need for blood transfusions in children and adults with sickle cell anemia (161,162). Observational studies have reported a reduction of TCD velocity (163165), rate of first stroke (166) and the rate of stroke recurrence (167170) in SCD patients treated with hydroxyurea. The Stroke With Transfusions Changing to Hydroxyurea (SWiTCH) trial, was a randomized, non-inferiority trial comparing transfusions and iron chelation to hydroxyurea and therapeutic phlebotomy for children with sickle cell anemia, stroke, and iron overload, with a composite primary endpoint allowing an increased stroke risk but requiring superiority for removing iron (171).…”
Section: Effect Of Disease Modifying Treatments Anticoagulants Anmentioning
confidence: 99%
“…In Jamaica, stroke is common in this population, with a cumulative incidence of 7·8% by the age of 14 years (Balkaran et al , ). The fact that this complication occurs more frequently in early childhood (Adams, ) makes the consequences more devastating, as stroke may affect motor function, development and cognition (Jordan et al , ), thus causing significant burden on the patient, their family and caregivers, as well as the country's health budget (Cunningham‐Myrie et al , ).…”
mentioning
confidence: 99%
“…Comparably, in studies of patients with SCA and abnormal TCD from Nigeria, children who took hydroxyurea did not experience excessive toxicity compared with those not treated with hydroxyurea . Furthermore, studies from other resource‐limited settings in India, Brazil, Jamaica, and Iraq demonstrated few adverse effects, and beneficial laboratory and clinical effects on hemoglobin, rates of transfusions, pain, and acute chest syndrome, similar to those found in children treated in North America and Europe.…”
Section: Discussionmentioning
confidence: 69%
“…Comparably, in studies of patients with SCA and abnormal TCD from Nigeria, children who took hydroxyurea did not experience excessive toxicity compared with those not treated with hydroxyurea. 49,52 Furthermore, studies from other resource-limited settings in India, [53][54][55] Brazil, 56 Jamaica, 48,57,58 56 and Ferster et al 6 observed mean hemoglobin increases of 0.3 and 0.6 g/dL, respectively. In contrast, studies such as the HUG-KIDS trial that gradually increased hydroxyurea to maximum tolerated dose in all subjects reported higher hydroxyurea-induced HGB and MCV than those found in our study.…”
Section: Hematological Toxicitymentioning
confidence: 96%